Pengaruh Penilaian Kinerja dan Manajemen Talenta terhadap Kinerja Pegawai Melalui Motivasi Kerja pada PT. Bank Negara Indonesia (Persero) Tbk Cabang Muara Bungo - irham, Irham; Syekh, Saiyid; Akbar, Ali (Universitas Batanghari, 2024)
This research is to describe performance assessment, talent management, work motivation and employee performance at PT. Bank Negara Indonesia (Persero) Tbk Muara Bungo Branch. From the tests carried out, it was found that work motivation was influenced by performance assessment and talent management by 0.698 or if the percentage was 69.8% while the rest was influenced by other variables. Employee performance in this case is also influenced by the performance assessment and talent management variables of 0.483 or if expressed as a percentage, it is 48.3%. From the results of hypothesis testing, it is known that talent management has no significant effect on employee performance at PT. Bank Negara Indonesia (Persero) Tbk Muara Bungo Branch with a p value of 0.281 or (0.281 > 0.05). This research concludes that performance assessment, talent management, work motivation and employee performance are in good and high condition. Apart from that, performance appraisal and talent management have a positive and significant effect on work motivation at PT. Bank Negara Indonesia (Persero) Tbk Muara Bungo Branch. Likewise, work motivation has a positive and significant influence on employee performance.